Experimental Study on the Mechanical Mechanism of Arch-Chord-Coupled Antisliding Structure - Guoping Hu; Yingzhi Xia; Mingxin Zheng; Hui Li; Xiaoxue Ruan (Geofluids)
Arch-chord-coupled antisliding structure is a new type of structure composed of multiple small-diameter piles for strengthening small- and medium-sized landslides, especially suitable for the reinforcement of slopes that are sensitive to deformation. In order to further explore the mechanical properties of the antisliding structure, physical model tests under four cases were carried out to study the deformation and stress characteristics of the structure under different types, and the optimal structural type was determined. The displacement test results show that even if there is no crown beam at the top of the piles, all the piles can deform in coordination, and when the number of rear piles is large, all the piles can basically deform synchronously. The test results of the bending moment of the pile body show that the crown beam has a great influence on the extreme value of the bending moment of each pile. For the structural type with more piles arranged in the rear row, the standard deviation of the extreme value of the bending moment of the pile body before and after adding the crown beam decreases from 2.0 to 1.03; the presence of crown beams effectively adjusts the internal force of each pile. The comprehensive analysis results show that the arch-chord-coupled antisliding structure with more piles in the rear row is the best.